Modeling the Cost-Effectiveness of Adjuvant Chemotherapy for Stage III Colon Cancer in South African Public Hospitals - Yoanna Pumpalova; Alexandra M. Rogers; Sarah Xinhui Tan; Candice-lee Herbst; Paul Ruff; Alfred I. Neugut; Chin Hur (JCO Global Oncology, 2021)
PURPOSECancer incidence is rising in low- and middle-income countries, where resource constraints often complicate therapeutic decisions. Here, we perform a cost-effectiveness analysis to identify the optimal adjuvant chemotherapy strategy for patients with stage III colon cancer treated in South African (ZA) public hospitals.METHODSA decision-analytic Markov model was developed to compare lifetime costs and outcomes for patients with stage III colon cancer treated with six adjuvant chemotherapy regimens in ZA public hospitals: fluorouracil, leucovorin, and oxaliplatin for 3 and 6 months; capecitabine and oxaliplatin (CAPOX) for 3 and 6 months; capecitabine for 6 months; and fluorouracil/leucovorin for 6 months. Transition probabilities were derived from clinical trials to estimate risks of toxicity, disease recurrence, and survival. Societal costs and utilities were obtained from literature. The primary outcome was the incremental cost-effectiveness ratio in international dollars (I$) per disability-adjusted life-year (DALY) averted, compared with no therapy, at a willingness-to-pay (WTP) threshold of I$13,006.56.RESULTSCAPOX for 3 months was cost-effective (I$5,381.17 and 5.74 DALYs averted) compared with no adjuvant chemotherapy. Fluorouracil, leucovorin, and oxaliplatin for 6 months was on the efficiency frontier with 5.91 DALYs averted but, with an incremental cost-effectiveness ratio of I$99,021.36/DALY averted, exceeded the WTP threshold.CONCLUSIONIn ZA public hospitals, CAPOX for 3 months is the cost-effective adjuvant treatment for stage III colon cancer. The optimal strategy in other settings may change according to local WTP thresholds. Decision analytic tools can play a vital role in selecting cost-effective cancer therapeutics in resource-constrained settings.